PKM Teknologi Fermentasi Tape Jusinta di Pondok Pesantren Puteri Yatama Mandiri Kabupaten Gowa - Nurhayani H. Muhiddin; Ratnawaty Mamin; Hasanuddin Hasanuddin (DEDIKASI, 2020)
The target partners in the Public Partnership Program (PKM) of Jusinta Tape Fermentation technology are students at the XII grade SMA Yatama Mandiri Islamic Boarding School, Gowa Regency. The location of the Islamic boarding school is in the area of Pallangga Subdistrict, Gowa Regency, which has the first highest cassava production and second highest sweet potatoes production land in South Sulawesi.. The implementation of activities is supported by the field of expertise of the implementing team related to the results of research in the form of a tape product called "Tape Jusinta" (Muhiddin, et al., 2018). This tape is made through the fermentation process of a mixture of purple sweet potato tubers and cassava roots using a local ragi tape starter. The process of making tape from purple sweet potato (Ipomoea batatas L.) and cassava roots (Manihot esculenta Crantz) with a local ragi tape starter, has received patent certificate in January 2020. Another thing that supports the potential of students who really need knowledge development and skills to grow economically productive businesses with Islamic boarding schools located in sweet potato and cassava production centers. The output target that is expected to be achieved in this PKM activity is that students have the knowledge and skills in producing Jusinta Tape through fermentation technology. The results of the activity are expected to be developed into a learning tool for biotechnology materials. The methods used are: lectures, demonstrations, discussions, practice and mentoring. The instruments used to determine the participants' responses to the Tape Jusinta fermentation technology training were questionnaires, observation, interviews, and documentation. The results achieved were that the participants could easily understand the processing of purple sweet potato and cassava roots into Tape Jusinta through fermentation technology. As many as 60% of the participants from the teacher group answered that the Tape Jusinta fermentation technology was in accordance with the students' abilities and was suitable to be applied in biotechnology learning. The organoleptic test results show that the Tape Jusinta product has a light purple color with an average of 4.4, the aroma of alcohol is less sharp with an average of 4.2, a soft texture with an average of 8.6, a slightly sour taste with an average of 4.4, the taste is quite sweet on average  6.5, and product palatability by the society is well received with an average of 8.9.